Educación ambiental sobre manejo de especies forestales nativas, en la escuela "12 de Julio" de la comunidad Balsa en medio de la microcuenca alta del Río Carrizal. - Chang Basurto, Andrea Katherine (2013)
The study was conducted in 2013 for the purpose of implementing environmental education processes in the management of native forest species, for strengthening the capacities of girls and boys in school, "July 12" Balsa community in the Middle of the micro Carrizal river's upper basin. The methodology used was that of farmer field schools, because it is a training methodology and participatory education which is based on the concept of discovery learning and applying ecological principles, and to adapt new knowledge to the participants. The results show that local capacities on environmental education in native forest species identified in ex before school participants studied rural area with little knowledge have weaknesses, same as at the end of the program (ex-post) showed strengthening, recognizing that species native forest, play an important role in environmental ecology as a fundamental part of biodiversity, to reduce the loss of forest areas for logging, decrease the advance of the agricultural frontier, to continue these processes will continue to cause impacts on flora, wildlife, soil and hence environmental quality of the environment. We conclude that educated environmental education to children and young people, using the participatory RCTs was a strategy to change behavior of the participants.